(3Ydh GdQJHI aj WdH GdMSHIs - (3GdYOhj GdTjRQj, CHh GdfLjH, LdGd GdOjf, YHO GdQMef Hf fUQ Hf YHO Gddg, fMh (B590 (3g`s ((3YeQ Hf YHO GdOGje GdTGejs)
(3ChdgG (B:s
(3GdMeO ddg Ydi eG CfYe abO SCdfj ef GSJfO Edi efUH GdMSHI hobdO GdfXQ aj eUGdM GdQYjI hcTa CMhGd GdShbI hCehQ GdeJYjTjf Cf CLeY dg eNJUQG cGajG dSdhc efgL GdMSHI Ydi GdhLg GdeSQhY djchf OdjdG dSjGSJg s
(3BNQgG (B:s
(3jLH Ydi GdeMJSH GRGdJg hGdefY ef aYdg heG CHGMJg GdTQjYI CbQg Ydi eG gh Ydjg hdgPG PcQfG aj Chd GdcJGH Cfg jLH Cf jchf GdeMJSH abjgG YGdeG HCMcGe GdTQjYI aeJi cGf GdeMJSH LGgdG GNJdaJ Ydjg GdCehQ hhbY aj GdeMPhQ hGdeMXhQ Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\340s
(3cTa GdXfhf (B2\1987s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdSjGSI hGdGLJeGYs